Association of fat-soluble vitamins (A, D, and E) status with humoral immune response to COVID-19 inactivated vaccination - Deng, Yao; Huang, Liting; Liu, Peixin; Geng, Xuyang; Lin, Zefang; Zheng, Zhixiong; Zhan, Meixiao; Zhang, Zhiren; Liu, Junwei; Sun, Taoping (Frontiers in Nutrition, 2023)
Background Fat-soluble vitamins (A, D, and E) are essential for the proper functioning of the immune system and are of central importance for infection risk in humans. Vitamins A, D, and E have been reported to be associated with the immune response following vaccination; however, their effects on the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination remain unknown. Methods We measured the neutralizing antibody titers against wild type and omicron within 98 days after the third homologous boosting shot of inactivated SARS-CoV-2 vaccine (BBIBP-CorV or CoronaVac) in 141 healthy adults in a prospective, open-label study. High-performance liquid chromatography-tandem mass spectroscopy was used to determine the concentrations of plasma vitamins A, D, and E. Results We found that the anti-wide-type virus and anti-omicron variant antibody levels significantly increased compared with baseline antibody levels (P < 0.001) after the third vaccination. 25(OH)D3 was significantly negatively associated with the baseline anti-wide-type virus antibody concentrations [beta (95% CI) = −0.331 (−0.659 ~ −0.003)] after adjusting for covariates. A potentially similar association was also observed on day 98 after the third vaccination [beta (95% CI) = −0.317 (−0.641 ~ 0.007)]. After adjusting for covariates, we also found that 25(OH)D3 was significantly negatively associated with the seropositivity of the anti-omicron variant antibody at day 98 after the third vaccination [OR (95% CI) = 0.940 (0.883 ~ 0.996)]. The association between plasma 25(OH)D3 with anti-wild-type virus antibody levels and seropositivity of anti-omicron variant antibodies were persistent in subgroup analyses. We observed no association between retinol/α-tocopherol and anti-wide-type virus antibody levels or anti-omicron variant antibody seropositive in our study. Conclusion The third inactivated SARS-CoV-2 vaccination significantly improved the ability of anti-SARS-CoV-2 infection in the human body. Higher vitamin D concentrations could significantly decrease the anti-wide-type virus-neutralizing antibody titers and anti-omicron variant antibody seropositive rate after the inactivated SARS-CoV-2 vaccination in people with adequate levels of vitamin D, better immune status, and stronger immune response; further studies comprising large cohorts of patients with different nutritional status are warranted to verify our results.